In the Wings - Bortolotti, Raphaël (Quellen und Forschungen aus italienischen Archiven und Bibliotheken, 2022)
Abstract The historical archive in Feltre (Veneto) preserves inventories of its Teatro Sociale that testify to this provincial theatre’s importance to the town and the surrounding area during the 19th century. These inventories are rare sources that have never previously been analysed. Based on these documents, this article investigates the world behind the scenes and extracts information on the staff involved in running the theatre. Offstage workers are generally forgotten on playbills and in theatre periodicals (which pay tribute to onstage artists and report the repertoire of travelling theatre companies), and they do not figure significantly in the documents of theatre companies such as contracts, correspondence and regulations. To a greater extent than other sources, these inventories provide a window onto the labour of these workers, who made a highly significant, if less visible, contribution to performances and the running of a theatre.